TRADITIONAL HANDICRAFTS OF UTTAR PRADESH - Gupta, Sunita; Verma, Ruchin (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Uttar Pradesh is famous for its art, craft, culture and spirituality form ancient time. It contributes in Indian economy by its art, crafts and culture. Beautiful shapes and colours of Zari Zardozi 's work of Bareilly, Budaun, Kasganj and Lucknow impress common people as well as richest. Ideal of gods and goddesses of Mathura craft are the symbols of Indian ideals, imagination, and sentiments. Due to the dence forest there are plenty of wood in Chitrakoot. Manufacturing of cheap and beautiful wooden toys has been going for thousands of years in Chitrakoot district. Khurja is famous for its white poetry that are the best examples of art and craft. Lucknow is famous for its Chikankari and hand block textile printing. Meenakari jewellery, stone work and silk sarees of Varanasi is well known in India as well as in foreign countries. Agra is famous for its leather work, stone work and engraving. Carpets designs of Bhadoi, handicrafts of Munj grass of Lakhimpur khiri and Prayagraj are marvelous. Brass items of Aligarh and Moradabad are also world famous. Kasganj, Firozabad, Mainpuri, Unnao, Hardoi, Shahjahanpur and Saharanpur are famous for its beautiful art and craft works.